111 / 5.000 Resultados de traducción Development of drip fertigation systems superficial located in the crop of gulupa under greenhouse - Carvajal Caballero, Rubén
In the fruit sector for export purposes in the province of García Rovira, in the department of Santander, there are low levels of efficiency in the use of water and nutrients supplied to crops such as cape gooseberry, passion fruit, the granadilla and for the specific case of this document the gulupa. In this regard, in the municipalities of Concepción and Molagavita, the design and implementation of superficial localized drip fertigation systems were carried out in the greenhouse cultivation of gulupa. First, the design of the irrigation system was carried out that allows the uniform distribution of water through dripping and later, the dosage of the mineral nutrition necessary for the crop was carried out according to its phenological stage and the nutritional requirements to have an irrigation plan and adequate fertilization for subsequent application through fertigation. As a result, 4 models were established in Concepción and 2 in Molagavita that promote the improvement of the production process and thus obtain higher productivity and better opportunities for access to markets and the producer's socioeconomic conditions. It is sought that through the technological extension process led by the Agribusiness and Tourism Center of the Andes (SENA-Malaga) replicate the models described to generate greater productivity and competitiveness of the products obtained in the productive projects of farmers and thus promote, the fruit sector in García Rovira